The Comparative Study of Art of Manufacturing Orosi and Stained Glass Windows in Iran and Europe - Mehrizi, Zahra Sadat Abooei; Marasy, Mohsen (Journal of History Culture and Art Research, 2017)
For a long time, glass manufacturing art has been globally common. There are certain similarities between Stained Glass and Orosi works. Based on historical texts, peak of Orosi art in Iran occurred during the reign of Safavid dynasty while its fall was after Qajar era. After introduction to churches after 12th century, Stained Glass manufacturing art was officially recognized. In contemporary era, Orosi art has almost faded away since it did not adapt to architecture. Similarly, Stained Glass art did not develop after it was introduced to Iran. The objectives of comparison between these arts are clarification of effects of the two arts on each other as well as better understanding of Orosi glass and Stained Glass arts. From methodological viewpoint, this study is descriptive-analytical in nature. In order to obtain better results, similar and available works of Orosi and Stained Glass arts were studied. The results of comparing these two arts suggested similar manufacturing methods and designs. In addition, a common application of the two arts is communication of greatness of the building to visitors’ minds. Stained Glass was mostly used for representation of Christ’s story while Orosi art was commonly used for depicting geometrical patterns. As a result, Orosi art was not initially influenced by Stained Glass art. In some cases, one could claim that Stained Glass art was influenced by Orosi art. Numerous factors played a role in creating differences between these two arts among which one could point to climatic conditions and patrons of such arts.